Surface and core temperature changes in Murrah buffaloes during cold weather conditions - DAS, S K; UPADHYAY, R C; MADAN, M L (The Indian Journal of Animal Sciences, 2013)
Six adult female Murrah buffaloes of 10-12 years age were exposed to winter conditions when minimum/maximum ambient temperature were 5.4/24.1oC. The skin temperature at forehead, middle pinna, neck, rump, forelegs, hindlegs was recorded using non-contact tempemture measuring instrument. Respiration mte and rectal temperature were measured throughout the 24 hr. The diurnal fluctuations and tempemture gradients have been reported for buffaloes. The changes in body temperature indicate that buffaloes during extreme cold conditions, in open area are not able to maintain their thermal equilibrium and, therefore, reduce temperature of appendages to conserve body heat effectively. Under such conditions adequate animal cover and protection from cold wind is essential.